완전 폐쇄성 대장암 환자에서 근치절제술의 치료 성적 - 이강홍(Kang Hong Lee); 유창식(Chang Sik Yu); 김희철(Hee Cheol Kim); 김정랑(Jung Rang Kim); 김영민(Young Min Kim); 김정선(Jung Sun Kim); 김진천(Jin Cheon Kim) (Annals of surgical treatment and research, 2004)
Purpose: A large bowel obstruction as a result of primary colorectal cancer has a poor outcome. A retrospective study was designed to verify the recurrence patterns and to determine the prognostic factors after a curative resection in patients with a completely obstructing colorectal cancer. Methods: Eight hundred patients with stage II and III colorectal adenocarcinomas (37 patients with a complete obstruction and 763 patients without an obstruction) underwent curative surgery between 1989 and 1996 at the Asan Medical Center. The median follow-up period was 55 (3～107) months. Results: Clinicopathologic variables, i.e. sex, serum carcinoembryonic antigen (CEA), Borrmann type, differentiation, and tumor stage in the two groups were similar. Patients with obstructing colorectal cancer were significantly older than those without an obstruction (61±14 vs. 56±12 years, P=0.02). Rectal cancers were more frequent in the non-obstructing cancers than in the obstructing cancers (P=0.02). The recurrence rate in the two groups was similar (obstructing vs. non-obstructing cancer, 27.0% vs. 28.0%). Ten patients with 12 recurrences were identified in 37 obstructing colorectal cancer patients, three with local recurrences (8.1%) and nine with distant metastasis (24.3%). The 5-year survival rate between the same stages was not different between the two groups (77.8% vs. 85.3% in stage II, 65.1% vs. 60.4% in stage III). Among the various clinicopathologic variables, neural invasion was strongly associated with a poor prognosis in obstructing colorectal cancer on multivariate analysis (P＜0.05). Conclusion: Because the obstructing cancers and the non-obstructing colorectal cancers had a similar outcome, curative surgery appears to offer the best chance of a cure in stage II and III obstructing colorectal cancer. KCI Citation Count: 2